(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the mechanisms of fostering creative thinking among university students through media education methods. In the context of modern educational reforms and the digital transformation of the learning process in Uzbekistan, media education emerges as a crucial pedagogical approach. The research investigates how targeted media-based tasks, audiovisual materials, and critical media analysis can stimulate students’ divergent thinking, imagination, and problem-solving abilities. By integrating media literacy into psychology and pedagogical courses, educators can create a dynamic learning environment that enhances both cognitive flexibility and emotional engagement. The paper also addresses the psychological foundations of creativity and their compatibility with media tools in higher education, particularly in teacher training institutions.